2018
DOI: 10.4314/gmj.v52i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for cervical cancer prevention and control in Ghana: public education and human papillomavirus vaccination

Abstract: SUMMARYGlobally, cervical cancer is a major public health issue causing increasing morbidity and mortality especially in lowand middle-income countries where preventive and control measures are lacking. In Ghana, it is the most common cancer among women. Approaches to reduce the incidence and mortality of the disease in Ghana have had little success due to lack of accurate data on the disease among other factors, to inform policies on prevention, early detection, diagnosis and treatment. Additionally, the lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
2
15
0
1
Order By: Relevance
“…In LMICs such as Ghana, it has been suggested that a mix of innovative screening methods tailored to the patient’s unique circumstances need to be employed for cervical cancer screening, if any gains are to be made in the fight to reduce the burden of cervical cancer [ 2 , 5 ]. Improving accessibility to cervical cancer screening is crucial to reducing the burden of cervical cancer in Ghana considering that there are reported disparities between various regions in the country [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In LMICs such as Ghana, it has been suggested that a mix of innovative screening methods tailored to the patient’s unique circumstances need to be employed for cervical cancer screening, if any gains are to be made in the fight to reduce the burden of cervical cancer [ 2 , 5 ]. Improving accessibility to cervical cancer screening is crucial to reducing the burden of cervical cancer in Ghana considering that there are reported disparities between various regions in the country [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been strategies to reduce the incidence of cancers in Ghana 25–27 ; however, the disease remains a threat to the health of the Ghanaian populace. Our current study was designed to examine the various types of cancers reported to hospitals in the Volta Region of Ghana with the aim of contributing to the cancer data in the country.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other reports from Ghana also identified breast, cervical, liver, and prostate cancers as the leading causes of cancer mortality. 8,17,25 HPV is the major cause of cervical cancer in Ghana, and the cancer accounts for about 8% of all cancer deaths in the country. 38 Globally, lung, colorectal, stomach, liver, and breast cancers result in the highest estimated deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The long waiting time to receive cytology results leads to loss of follow-up, which is a contributing factor to advanced stage diagnosis [88]. Poor funding, as cited by many East African countries, is congruent with several studies conducted in Africa on a lack of funding as a barrier to the control and prevention of cancer [63,89]. Populations of East African countries are not covered by a social healthcare system, where there is no universal access to most healthcare services, for example, HPV vaccination.…”
Section: Challenges and Solutionsmentioning
confidence: 94%